Association of TyG index with mortality at 28 days in sepsis patients in intensive care from MIMIC IV database - Heping Xu; Jinyuan Xie; Yan Xia; Huan Niu; Hong Wang; Feng Zhan (Scientific Reports)
Abstract The relationship between the triglyceride‒glucose (TyG) index and the clinical prognosis of septic patients in intensive care units (ICUs) remains unclear. This study aimed to explore the correlation between the TyG index and 28-day all-cause mortality in septic patients. A retrospective observational cohort study was conducted, including 8955 septic patients from the MIMIC IV 2.2 database. The primary outcome was 28-day all-cause mortality. Multivariate logistic regression analysis and restricted cubic spline regression analysis were used to assess the relationship between the TyG index and 28-day all-cause mortality in septic patients. Subgroup analyses and sensitivity analyses were performed to further validate the robustness of the results. A total of 8955 septic patients were included, 5219 (58.3%) of whom were male, with a mean age of 66.3 (15.8) years and an average TyG index of 9.08 (0.70) and the number of deaths within 28 days was 1639 (18.3%). The RCS curve demonstrated a U-shaped relationship between the TyG index and 28-day all-cause mortality (nonlinear P value = 0.0003). The risk of 28-day all-cause mortality was negatively associated with the TyG index until it decreased to 9.03 (adjusted odds ratio [OR] 0.727, 95% confidence interval [CI] 0.577–0.915). However, when the TyG index exceeded 9.03, the odds ratio for 28-day all-cause mortality significantly increased (adjusted OR 1.185, 95% CI 1.001–1.404). These findings were consistent across subgroups and various sensitivity analyses. Our study revealed a nonlinear U-shaped relationship between the TyG index and 28-day all-cause mortality, with a critical point at a TyG index of 9.03. Our results suggest that the TyG index may be a novel and important factor for the short-term clinical prognosis of critically ill septic patients.